Design and fabrication of portable cleaning machine for raw edible bird's nest - Yap, Wei Keong (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Edible bird's nest is one of the demanding food products. Removing the impurities in raw edible bird's nest is generally known as the most complcated cleaning process especially for grade C raw edible bird's nest. Conventional cleaning method is not efficiency, time- consumingand requires large workforce to process small quantities of edible bird's nests.